Effect of Stearic Acid on Barrier and Mechanical Properties of Edible Films Based on Carboxymethyl Cellulose (CMC), Konjac Glucomannan (KGM), and κ-Carrageenan (κCarr) - Widyasti, Lintang Dian; Meka, Wahyu; Nurkhamidah, Siti (Eksergi, 2025)
The development of edible films using natural polysaccharides presents a sustainable alternative to synthetic packaging materials. This study aimed to enhance the barrier properties of edible films composed of carboxymethyl cellulose (CMC), konjac glucomannan (KGM), and κ-carrageenan (κCarr) by incorporating stearic acid (SA). Films were prepared by blending the biopolymers with SA at varying concentrations (0.1–0.5% w/w) and characterized for their structural, physical, and mechanical properties. Fourier-transform infrared (FTIR) spectroscopy confirmed molecular interactions between SA and the polysaccharide matrix, evidenced by reduced O–H absorption bands and intensified –CH₂– peaks. SA incorporation increased film thickness and moisture content but reduced tensile strength, elongation at break, solubility, and water vapor permeability (WVP). Although the WVP of SA-modified films did not meet the Japanese Industrial Standard at the tested concentrations, the observed trend suggests that higher SA levels could further improve barrier performance. The optimal formulation (0.5% SA) demonstrated enhanced hydrophobicity, acceptable water activity, and moderate tensile strength and opacity. These findings indicate that stearic acid can effectively modify the functional properties of polysaccharide-based edible films, advancing their potential as eco-friendly food packaging materials. Further optimization of SA concentration is recommended to achieve industrial moisture barrier standards.